Progress on the HIF-1α/VEGF/VEGFR2 signal pathway in hepatic alveolar echinococcosis - Xu, Meng-Zhao; Ke, Fei; Chai, Jin-Ping; A, Ji-De; Tan, Qing-Long (Frontiers in Oncology, 2025)
Alveolar echinococcosis (AE), a lethal parasitic zoonosis mimicking malignant tumors, progresses via hepatic infiltration and metastatic spread, causing multiorgan failure. Despite its clinical resemblance to cancer, molecular drivers of its aggressiveness remain poorly defined. Recent studies highlight perilesional angiogenesis as pivotal for lesion invasiveness, mediated by VEGF-driven pathological vascularization. VEGF not only fuels parasitic proliferation by creating nutrient-rich microenvironments but also engages crosstalk with host-parasite interactions, including immune evasion by Echinococcus multilocularis, germinal layer hyperplasia, and periparasitic inflammation.Targeting the HIF-1α/VEGF/VEGFR2 axis emerges as a promising therapeutic strategy. Mechanistically, VEGF/VEGFR2 blockade may simultaneously disrupt angiogenesis-dependent parasitic expansion and survival pathways. Preclinical evidence shows that inhibiting HIF-1α (VEGF’s upstream regulator) suppresses metacestode proliferation and tissue invasion by starving lesions of vascular support while modulating immune-inflammatory responses. This dual action addresses both parasitic resource acquisition and host defence subversion.This review synthesizes molecular insights into HIF-1α/VEGF-mediated pathogenesis with clinical observations, proposing anti-angiogenic therapy as a rational adjunct to current treatments. By delineating VEGF’s role in sustaining parasitic metabolic demands and immune regulation, we underscore the translational potential of pathway-specific inhibitors. Such approaches could mitigate limitations of conventional therapies (e.g., benzimidazoles), particularly for advanced-stage AE with microvascular proliferation. Systematic analysis of angiogenesis signalling networks advances our understanding of AE’s “parasitic cancer” paradigm while guiding development of targeted interventions to improve patient outcomes.